Arancino.ccTM: an open hardware platform for urban regeneration. (5th October 2020) - Giacobbe, Maurizio; Alessi, Francesco; Zaia, Angelo; Puliafito, Antonio
The term 'metabolism' identifies the set of chemical processes that occur within a living organism in order to maintain its life. By analogy, we use the 'urban metabolism' concept showing the life of a city. A city is a set of very complex processes involving both public and private stakeholders, areas and infrastructures. Urban metabolism can be analysed and therefore its status evaluated based on measuring specific parameters in order to offer sustainable services for people. The internet of things (IoT) paradigm helps the collection of large amounts of data that become available for decision makers and city managers to improve the urban metabolism. Based on these consideration, in this paper we present and discuss the Arancino.cc TM architecture, in order to achieve 'green' benefits: a better quality of life, a more efficient city management also optimising energy consumptions and costs.